Lithium secondary battery
Patent Information
- Application Number
- JP2023524199
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2022-07-06
- Filing Date
- 2022-07-07
- Publication Date
- 2025-03-11
- Estimated Expiration
- 2042-07-07
AI Technical Summary
【0015】 本発明のリチウム二次電池は、固体状態の硝酸リチウム保有体を含むことにより、電池駆動中、持続的に硝酸リチウムを供給することができて、長いサイクルの間高いクーロン効率を維持できる。
Smart Images

Figure 0007644230000002 
Figure 0007644230000003 
Figure 0007644230000004
Abstract
Description
[Technical field]
[0001] This application claims the benefit of priority based on Korean Patent Application No. 10-2021-0091398 filed on July 13, 2021 and Korean Patent Application No. 10-2022-0082998 filed on July 6, 2022, and incorporates all contents disclosed in the documents of said Korean patent applications as part of this specification.
[0002] The present invention relates to a lithium secondary battery containing a solid-state lithium nitrate carrier. [Background technology]
[0003] Recently, electronic devices and communication devices have been rapidly becoming smaller, lighter, and more powerful, and the need for electric vehicles has increased in relation to environmental issues. As a result, there is a strong demand for improved performance of secondary batteries that can be used as energy sources for these products. As a secondary battery that meets such demands, much research has been conducted on lithium-sulfur batteries that use sulfur-based materials as the positive electrode active material.
[0004] A lithium-sulfur battery is a secondary battery that uses a sulfur-based compound containing a sulfur-sulfur bond as a positive electrode active material and a carbon-based material in which insertion / deintercalation of an alkali metal such as lithium or a metal ion such as lithium ion occurs as a negative electrode active material.
[0005] In particular, the theoretical discharge capacity of lithium-sulfur batteries is 1,675mAh / g and the theoretical energy density is 2,600Wh / kg, which is about five times higher than the lithium-ion batteries (about 570Wh / kg) currently being researched, making it possible to realize high capacity, high energy density, and long life. In addition, sulfur, the main material of the positive electrode active material, has low atomic weight, is abundant in resources, easy to supply and demand, is inexpensive, and is non-toxic and environmentally friendly. Due to these advantages, lithium-sulfur batteries are attracting attention as an energy source for not only portable electronic devices but also medium-sized and large devices such as electric vehicles.
[0006] Specifically, an oxidation reaction of lithium occurs at the negative electrode of a lithium-sulfur battery, while a reduction reaction of sulfur occurs at the positive electrode. Before discharging, sulfur has a cyclic S8 structure, but during the reduction reaction (discharging), sulfur-sulfur bonds are broken, decreasing the oxidation number of sulfur, and during the oxidation reaction (charging), sulfur-sulfur bonds are re-formed, increasing the oxidation number of sulfur. Electrical energy is stored and generated by using this oxidation-reduction reaction. During this electrochemical reaction, sulfur is reduced from the cyclic S8 to a linear lithium polysulfide (Li2S x , x=8,6,4,2), and when these lithium polysulfides are completely reduced, lithium sulfide (Li2S) is finally produced. Due to the process of reduction to each lithium polysulfide, the discharge behavior of lithium-sulfur batteries shows a stepwise discharge voltage, unlike lithium-ion batteries.
[0007] Among the lithium polysulfides such as Li2S8, Li2S6, Li2S4, and Li2S2, which are intermediate products of the electrochemical reaction in lithium-sulfur batteries, lithium polysulfides with a high sulfur oxidation number (Li2S x , usually x>4) is a highly polar substance and easily dissolves in electrolytes containing hydrophilic organic solvents. Lithium polysulfide dissolved in the electrolyte diffuses from the positive electrode due to the concentration difference. The lithium polysulfide dissolved from the positive electrode in this way leaves the electrochemical reaction area of the positive electrode and is unable to be gradually reduced to lithium sulfide (Li2S). In other words, lithium polysulfide that is dissolved in the electrolyte after leaving the positive electrode cannot participate in the charge and discharge reaction of the battery, which causes the loss of sulfur used as a positive electrode active material, and is the main cause of the decrease in capacity and lifespan of lithium-sulfur batteries.
[0008] In addition, the eluted lithium polysulfide may undergo a shuttle reaction in which it is directly reacted with the surface of the negative electrode to be reduced and then oxidized again on the surface of the positive electrode. The shuttle reaction reduces the discharge capacity and increases the charge capacity, which causes a problem of reducing the coulomb efficiency, which is the ratio of the discharge capacity to the charge capacity.
[0009] To solve this problem, a method of adding an additive to the electrolyte was studied, but the additive was gradually consumed as the cycle progressed, and after the additive was completely consumed, the coulombic efficiency rapidly decreased.
[0010] Therefore, there is a demand for the development of a lithium secondary battery that can maintain a high coulombic efficiency over a long period of cycles. [Prior art documents] [Patent documents]
[0011] [Patent Document 1] Republic of Korea Patent Publication No. 10-2015-0032670 Summary of the Invention [Problem to be solved by the invention]
[0012] Therefore, the present inventors have conducted extensive research to solve the above problems, and have confirmed that when a solid-state lithium nitrate holder is included in a lithium secondary battery, lithium nitrate is continuously supplied during battery operation, and high coulombic efficiency is maintained over a long cycle, thereby completing the present invention.
[0013] It is therefore an object of the present invention to provide a lithium secondary battery capable of maintaining a high coulombic efficiency over a long period of cycling. [Means for solving the problem]
[0014] In order to achieve the above objective, The present invention relates to a cell stack including one or more unit cells each including a positive electrode, a negative electrode, and a separator interposed between the positive electrode and the negative electrode; A solid-state lithium nitrate carrier, Electrolyte, and A lithium secondary battery is provided, comprising the cell stack, a solid-state lithium nitrate holder, and a battery case containing an electrolyte. Effect of the Invention
[0015] The lithium secondary battery of the present invention contains a solid-state lithium nitrate host, and thus can continuously supply lithium nitrate during battery operation, thereby maintaining high coulombic efficiency over a long cycle. [Brief description of the drawings]
[0016] [Figure 1] 1 is a schematic diagram showing the structure of a lithium secondary battery of the present invention. [Diagram 2] FIG. 1 is a schematic diagram showing the structure of a conventional lithium secondary battery. [Diagram 3] 1 is a photograph of a lithium nitrate-containing film before operation of a lithium secondary battery. [Figure 4] 1 is a photograph of a lithium nitrate-containing film after being operated with a lithium secondary battery. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0017] The present invention will now be described in more detail.
[0018] In lithium secondary batteries, especially lithium-sulfur batteries, lithium polysulfide may dissolve into the electrolyte during charging and discharging, causing a shuttle phenomenon, which reduces the discharge capacity and increases the charge capacity, resulting in a decrease in coulombic efficiency, which is the ratio of discharge capacity to charge capacity.
[0019] In the past, in order to prevent the shuttle phenomenon, attempts were made to maintain high coulombic efficiency during long cycles by using lithium nitrate (LiNO3) as an additive to the electrolyte. However, as the cycles proceed, lithium nitrate is gradually consumed, and there is a problem that the coulombic efficiency drops sharply after all the lithium nitrate is consumed. Since the solubility of lithium nitrate in the electrolyte is limited, it is impossible to add lithium nitrate to the electrolyte in an amount that can be used during long cycles. Therefore, the use of lithium nitrate as an additive to the electrolyte has a problem that the number of cycles during which high coulombic efficiency can be maintained is short.
[0020] Therefore, the present invention aims to provide a lithium secondary battery capable of maintaining a high coulombic efficiency over a long period of cycles.
[0021] That is, the present invention relates to a cell stack 10 including one or more unit cells each including a positive electrode 20, a negative electrode 40, and a separator 30 interposed between the positive electrode and the negative electrode; Solid-state lithium nitrate carrier 50, Electrolyte, and The present invention relates to a lithium secondary battery including the cell stack, a solid-state lithium nitrate holder, and a battery case containing an electrolyte.
[0022] In the present invention, the solid-state lithium nitrate holder can continuously supply lithium nitrate during the operation of the lithium secondary battery. Therefore, it is possible to prevent a decrease in coulombic efficiency due to a decrease in lithium nitrate, and to maintain a high coulombic efficiency during a long cycle. Generally, a long cycle means 200 cycles or more, and a high coulombic efficiency means 98% or more.
[0023] The solid-state lithium nitrate holder 50 may be located on one or both sides of the outermost layer of the cell stack, which may be located in the space between the battery case and the cell stack.
[0024] If the lithium nitrate host is located inside the cell stack, the lithium nitrate host may act as a factor that increases the resistance of the battery and deteriorate the performance of the battery. The lithium nitrate host is located inside the cell stack means that the lithium nitrate host is located between the positive electrode and the separator or between the negative electrode and the separator.
[0025] Specifically, the physical structure of the lithium nitrate host may narrow the material transfer path between the negative and positive electrodes, hindering material transfer. In addition, the thickness of the lithium nitrate host may increase the distance between the positive and negative electrodes, increasing the distance that materials must travel when the battery is in operation. Therefore, when the lithium nitrate host is located inside the cell stack, the lithium nitrate host may act as a factor that increases resistance. The increase in resistance may cause overvoltage when the battery is in operation, reducing the energy of the battery, and may cause problems such as a decrease in the maximum dischargeable current, deteriorating output characteristics.
[0026] However, if the lithium nitrate holder is located on one or both sides of the outermost layer of the cell stack, it does not structurally impede material transfer between the positive and negative electrodes, and does not increase the distance between the positive and negative electrodes, so it can serve to supply lithium nitrate as an electrolyte without increasing resistance.
[0027] The solid-state lithium nitrate carrier may be a lithium nitrate-containing film (LiNO3film).
[0028] The lithium nitrate-containing film may be a film prepared by mixing lithium nitrate and a binder, or a film in which a coating layer is formed by coating one or both sides of a separate substrate film with a coating composition containing lithium nitrate and a binder.
[0029] According to an embodiment of the present invention, the lithium nitrate-containing film may be a film containing lithium nitrate and a binder in a solid content weight ratio of 80:20 to 98:2, or a film in which a coating layer containing lithium nitrate and a binder in a solid content weight ratio of 80:20 to 98:2 is formed on one or both sides of a separate substrate film.
[0030] Specifically, within the weight ratio range, the lithium nitrate may be 80 or more, 85 or more, 90 or more, 93 or more, 95 or more, 97 or more, 85 or less, 90 or less, 93 or less, 95 or less, or 98 or less. Also, the binder may be 2 or more, 5 or more, 7 or more, 10 or more, 12 or more, 15 or more, 17 or more, 19 or more, 3 or less, 5 or less, 7 or less, 10 or less, 12 or less, 15 or less, 17 or less, or 20 or less.
[0031] If the binder is contained in an amount less than the above weight ratio, lithium nitrate is not fixed to the film and is detached. If the binder is contained in an amount exceeding the above weight ratio, the weight of the coating layer increases when the same weight of lithium nitrate is applied to the film due to the excessive amount of binder, and the energy density of the lithium secondary battery may be reduced.
[0032] In addition, if the lithium nitrate is contained in an amount less than the above weight ratio, it is difficult to maintain a high coulombic efficiency during a long cycle due to the low lithium nitrate content, and if the lithium nitrate is contained in an amount more than the above weight ratio, the lithium nitrate may be detached or coating may be difficult due to the low binder content.
[0033] The substrate film may be of any type as long as it is used in the art. For example, aluminum foil (Al foil), copper foil (Cu foil), polyethylene (PE), polyethylene terephthalate (PET), polyimide (PI), etc. may be used.
[0034] The binder serves to hold the lithium nitrate in the film. The binder may be any of various types of binders, such as polyvinylidene fluoride-hexafluoropropylene (PVDF-co-HFP), polyvinylidene fluoride (PVDF), polyacrylonitrile, polymethyl methacrylate, styrene butadiene rubber (SBR), polyacrylic acid, carboxyl methyl cellulose (CMC), etc., and preferably carboxyl methyl cellulose may be used.
[0035] The coating composition may further include a solvent, and the solvent may be included in an amount of 50 to 90 wt % based on the total weight of the coating composition.
[0036] The coating composition may be coated on one or both sides of a substrate film and then dried.
[0037] The drying can be carried out at a temperature of 30 to 80°C, preferably at a temperature of 40 to 60°C.
[0038] If the drying temperature is less than 30°C, the solvent will not be sufficiently dried and it will be impossible to form a lithium nitrate film. If the drying temperature exceeds 80°C, the drying speed will be too fast, making the film porous and causing the lithium nitrate to be released.
[0039] The drying time may be the time it takes for the aqueous solution to be sufficiently dried, and may be 2 to 8 hours, but is not limited thereto.
[0040] After the drying, a secondary drying may be additionally performed. The secondary drying may be performed at a temperature of 50 to 150° C. for 15 to 30 hours. By performing the secondary drying, the moisture content of the lithium nitrate-containing film may be reduced, thereby suppressing the degradation of the lithium secondary battery due to moisture.
[0041] After drying, the lithium nitrate-containing film may be rolled to finally produce a lithium nitrate-containing film.
[0042] The positive electrode 20 may include a positive electrode current collector and a positive electrode active material layer coated on one or both sides of the positive electrode current collector.
[0043] The positive electrode current collector is not particularly limited as long as it has high conductivity without inducing a chemical change in the battery, and may be, for example, stainless steel, aluminum, nickel, titanium, calcined carbon, or aluminum or stainless steel surface-treated with carbon, nickel, titanium, silver, etc. In this case, the positive electrode current collector may be in various forms such as a film, sheet, foil, net, porous body, foam, nonwoven fabric, etc., having fine irregularities formed on the surface so as to increase the adhesive strength with the positive electrode active material.
[0044] The positive electrode active material layer includes a positive electrode active material, and may further include a conductive material, a binder, an additive, and the like.
[0045] The positive electrode active material contains sulfur, specifically, elemental sulfur (S8), organic sulfur compounds (Li2S n (n≧1)), and carbon-sulfur polymers ((C2S x ) n (x=2.5 to 50, n≧2). Preferably, the positive electrode active material may be inorganic sulfur. Therefore, the lithium secondary battery of the present invention may be a lithium-sulfur battery.
[0046] The sulfur contained in the positive electrode active material does not have electrical conductivity by itself, and is therefore used in a composite with a conductive material such as a carbon material. Thus, the sulfur is contained in the form of a sulfur-carbon composite, and preferably, the positive electrode active material may be a sulfur-carbon composite.
[0047] The carbon contained in the sulfur-carbon composite is a porous carbon material that provides a framework to which the sulfur can be uniformly and stably fixed, and complements the low electrical conductivity of sulfur to facilitate smooth electrochemical reactions.
[0048] The porous carbon material may be generally prepared by carbonizing various carbon precursors. The porous carbon material includes non-uniform pores, the average pore diameter of which may be in the range of 1-200 nm, and the porosity or porosity of the porous carbon material may be in the range of 10-90% of the total volume of the porous carbon material. If the average pore diameter is less than the range, the pore size is merely at the molecular level and impregnation with sulfur is impossible, whereas if the average pore diameter exceeds the range, the mechanical strength of the porous carbon material is weakened and it is not suitable for use in the manufacturing process of an electrode.
[0049] The shape of the porous carbon material may be spherical, rod-like, needle-like, plate-like, tubular or bulk-like, and any shape commonly used in lithium-sulfur batteries may be used without limitation.
[0050] The porous carbon material may be any material commonly used in the art that has a porous structure or a high specific surface area. For example, the porous carbon material may be at least one selected from the group consisting of graphite, graphene, carbon black such as denka black, acetylene black, ketjen black, channel black, furnace black, lamp black, and thermal black, carbon nanotubes (CNTs) such as single-walled carbon nanotubes (SWCNTs) and multi-walled carbon nanotubes (MWCNTs), carbon fibers such as graphite nanofibers (GNFs), carbon nanofibers (CNFs), and activated carbon fibers (ACFs), graphite such as natural graphite, artificial graphite, and expanded graphite, and activated carbon, but is not limited thereto. Preferably, the porous carbon material may be carbon nanotubes.
[0051] The sulfur-carbon composite may contain 60 to 90 parts by weight, preferably 65 to 85 parts by weight, and more preferably 70 to 80 parts by weight of sulfur based on 100 parts by weight of the sulfur-carbon composite. If the sulfur content is less than the above range, the content of the porous carbon material in the sulfur-carbon composite is relatively high, which increases the specific surface area and increases the content of the binder during the preparation of the positive electrode. Such an increase in the amount of binder used may ultimately increase the surface resistance of the positive electrode and act as an insulator that hinders electron pass, thereby deteriorating the performance of the battery. On the other hand, if the sulfur content exceeds the above range, the sulfur that could not be bonded to the porous carbon material may solidify or re-dissolve on the surface of the porous carbon material, making it difficult for the sulfur to receive electrons and therefore unable to participate in the electrochemical reaction, resulting in a loss of capacity of the battery.
[0052] In addition, in the sulfur-carbon composite, the sulfur is located at least in one of the inner and outer surfaces of the porous carbon material, and may be present in less than 100%, preferably 1 to 95%, and more preferably 60 to 90% of the entire inner and outer surfaces of the porous carbon material. When the sulfur is present in the inner and outer surfaces of the porous carbon material within the above range, the maximum effect can be obtained in terms of the electron transfer area and wettability with the electrolyte. Specifically, in the above range, the sulfur is thinly and uniformly impregnated into the inner and outer surfaces of the porous carbon material, so that the electron transfer contact area can be increased during charging and discharging. If the sulfur is located in 100% of the entire inner and outer surfaces of the porous carbon material, the carbon material is completely covered with sulfur, which reduces the wettability with the electrolyte and reduces the contact with the conductive material contained in the electrode, making it impossible to transfer electrons and to participate in the electrochemical reaction.
[0053] The method for preparing the sulfur-carbon composite is not particularly limited in the present invention, and may be a method commonly used in the art. For example, the sulfur and the porous carbon material may be simply mixed and then heat-treated to prepare a composite.
[0054] In addition to the above-mentioned composition, the positive electrode active material may further include one or more additives selected from a transition metal element, a Group IIIA element, a Group IVA element, sulfur compounds of these elements, and alloys of these elements with sulfur.
[0055] The transition metal elements may include Sc, Ti, V, Cr, Mn, Fe, Co, Ni, Cu, Zn, Y, Zr, Nb, Mo, Tc, Ru, Rh, Pd, Os, Ir, Pt, Au, or Hg, and the IIIA group elements may include Al, Ga, In, or Tl, and the IVA group elements may include Ge, Sn, or Pb.
[0056] The positive electrode active material may be included in an amount of 40 to 95 wt%, preferably 45 to 90 wt%, and more preferably 60 to 90 wt%, based on 100 wt% of the entire positive electrode active material layer constituting the positive electrode. If the content of the positive electrode active material is less than the above range, it is difficult to fully exert the electrochemical reaction of the positive electrode, and conversely, if it exceeds the above range, the contents of the conductive material and binder described below are relatively insufficient, which increases the resistance of the positive electrode and deteriorates the physical properties of the positive electrode.
[0057] The positive electrode active material layer may further include a conductive material for allowing electrons to move smoothly within the positive electrode (specifically, the positive electrode active material) and a binder for better adhesion of the positive electrode active material to the current collector.
[0058] For example, the conductive material may be carbon black such as Super-P, Denka Black, acetylene black, Ketjen Black, channel black, furnace black, lamp black, or thermal black; carbon derivatives such as carbon nanotubes, graphene, or fullerene; conductive fibers such as carbon fibers or metal fibers; metal powders such as carbon fluoride, aluminum, or nickel powder; or conductive polymers such as polyaniline, polythiophene, polyacetylene, or polypyrrole, which may be used alone or in combination.
[0059] The binder supports the positive electrode active material on the positive electrode current collector and organically connects the positive electrode active materials to enhance the binding strength therebetween, and any binder known in the art may be used. The binder is as described above.
[0060] In the present invention, the method for manufacturing the positive electrode is not particularly limited, and any method known to those skilled in the art or various methods modified therefrom may be used.
[0061] For example, the positive electrode may be manufactured by preparing a positive electrode slurry composition including the above-mentioned composition and then coating the composition on at least one surface of the positive electrode current collector.
[0062] The positive electrode slurry composition includes the positive electrode active material, the conductive material, and the binder, and may further include a solvent.
[0063] The solvent is one that can uniformly disperse the positive electrode active material, the conductive material, and the binder. As the solvent, water is most preferable as an aqueous solvent, and the water may be distilled water or deionized water. However, the solvent is not necessarily limited thereto, and if necessary, a lower alcohol that can be easily mixed with water may be used. The lower alcohol may be methanol, ethanol, propanol, isopropanol, butanol, etc., and preferably, these may be mixed with water before use.
[0064] The content of the solvent may be at a level having a concentration that allows easy coating, and the specific content varies depending on the coating method and device.
[0065] The positive electrode slurry composition may further include, as necessary, a substance commonly used in the relevant technical field for the purpose of improving its function, etc., such as a viscosity modifier, a fluidizing agent, a filler, etc.
[0066] The method of applying the positive electrode slurry composition is not particularly limited in the present invention, and may include, for example, methods such as doctor blade, die casting, comma coating, screen printing, etc. In addition, the positive electrode slurry may be applied onto the positive electrode current collector by a pressing or lamination method after forming the positive electrode slurry on a separate substrate.
[0067] After the coating, a drying process may be performed to remove the solvent. The drying process is performed at a temperature and time level that allows the solvent to be sufficiently removed, and the conditions may vary depending on the type of solvent, and are not particularly limited in the present invention. Examples include drying with warm air, hot air, or low-humidity air, vacuum drying, and drying by irradiation with (far) infrared rays and electron beams. The drying speed is usually adjusted so that the solvent can be removed as quickly as possible within a range of speeds that do not cause cracks in the positive electrode active material layer due to stress concentration or cause the positive electrode active material layer to peel off from the positive electrode current collector.
[0068] Additionally, after the drying, the current collector may be pressed to increase the density of the positive electrode active material in the positive electrode. Examples of the pressing method include die pressing and roll pressing.
[0069] The negative electrode 40 may be composed of a current collector and a negative electrode active material layer formed on one or both sides of the current collector, or the negative electrode may be a lithium metal plate.
[0070] The current collector is for supporting the negative electrode active material, and is not particularly limited as long as it has excellent conductivity and is electrochemically stable in the voltage region of the lithium secondary battery. For example, copper, stainless steel, aluminum, nickel, titanium, palladium, calcined carbon, copper or stainless steel surface treated with carbon, nickel, silver, etc., aluminum-cadmium alloy, etc. may be used.
[0071] The negative electrode current collector may have fine irregularities on its surface to strengthen the bonding force with the negative electrode active material, and may be in various forms such as a film, a sheet, a foil, a mesh, a net, a porous body, a foam, a nonwoven fabric, etc.
[0072] The negative electrode active material may be a material capable of reversibly intercalating or deintercalating lithium ions, a material capable of reversibly forming a lithium-containing compound by reacting with lithium ions, lithium metal, or a lithium alloy.
[0073] The material capable of reversibly intercalating or deintercalating lithium ions may be, for example, crystalline carbon, amorphous carbon, or a mixture thereof.
[0074] The material capable of reacting with lithium ions to reversibly form a lithium-containing compound can be, for example, tin oxide, titanium nitrate, or silicon.
[0075] The lithium alloy may be, for example, an alloy of lithium (Li) and a metal selected from the group consisting of sodium (Na), potassium (K), rubidium (Rb), cesium (Cs), francium (Fr), beryllium (Be), magnesium (Mg), calcium (Ca), strontium (Sr), barium (Ba), radium (Ra), aluminum (Al), and tin (Sn).
[0076] A separator 30 may additionally be included between the positive and negative electrodes.
[0077] The separator separates or insulates the positive electrode and the negative electrode from each other and enables lithium ion transport between the positive electrode and the negative electrode, and may be made of a porous non-conductive or insulating material. The separator may be an independent member such as a film, or may be a coating layer added to the positive electrode and / or the negative electrode.
[0078] The separation membrane is preferably one that has low resistance to the ion migration of the electrolyte and has excellent moisture-absorbing capacity for the electrolyte.
[0079] The separator may be made of a porous substrate. The porous substrate may be any porous substrate commonly used in secondary batteries. A porous polymer film may be used alone or in combination. For example, a nonwoven fabric made of high melting point glass fiber, polyethylene terephthalate fiber, or the like, or a polyolefin-based porous membrane may be used, but is not limited thereto.
[0080] The material of the porous substrate is not particularly limited in the present invention, and any porous substrate generally used in electrochemical devices may be used. For example, the porous substrate may be made of a material selected from the group consisting of polyolefins such as polyethylene and polypropylene, polyesters such as polyethyleneterephthalate and polybutyleneterephthalate, polyamides, polyacetals, polycarbonates, polyimides, polyetheretherketones, polyethersulfones, polyphenyleneoxides, polyphenylenesulfides, polyethylenenaphthalates, polytetrafluoroethylenes, polyvinylidene fluorides, polyvinyl chlorides, and the like. The material may include one or more materials selected from the group consisting of poly(p-phenylene benzobisoxazole), polyacrylonitrile, cellulose, nylon, poly(p-phenylene benzobisoxazole), and polyarylate.
[0081] The thickness of the porous substrate is not particularly limited, and may be 1 to 100 μm, preferably 5 to 50 μm. The thickness range of the porous substrate is not limited to the above range, but if the thickness is smaller than the above lower limit, the mechanical properties may be deteriorated and the separator may be easily damaged during use of the battery.
[0082] The average diameter and porosity of the pores present in the porous substrate are also not particularly limited, but may be 0.001 to 50 μm and 10 to 95%, respectively.
[0083] The electrolyte contains lithium ions and serves to cause an electrochemical oxidation or reduction reaction between the positive electrode and the negative electrode using the lithium ions as a medium.
[0084] The electrolyte may be a non-aqueous electrolyte or a solid electrolyte that does not react with lithium metal, but is preferably a non-aqueous electrolyte that includes an electrolyte salt and an organic solvent.
[0085] The electrolyte salt contained in the non-aqueous electrolyte is a lithium salt. The lithium salt may be any salt commonly used in electrolytes for lithium secondary batteries. For example, LiCl, LiBr, LiI, LiClO4, LiBF4, LiB 10 Cl 10 , LiPF6, LiCF3SO3, LiCF3CO2, LiC4BO8, LiAsF6, LiSbF6, LiAlCl4, CH3SO3Li, CF3SO3Li, (CF3SO2)2NLi, (C2F5SO2)2NLi, (SO2F)2NLi, (CF3SO2)3CLi, lithium chloroborane, lithium lower aliphatic carboxylates, lithium 4-phenylborate, lithium imide, and the like may be used.
[0086] The concentration of the lithium salt may be appropriately determined in consideration of ion conductivity, solubility, etc., and may be, for example, 0.1 to 4.0 M, preferably 0.5 to 2.0 M. If the concentration of the lithium salt is below this range, it is difficult to ensure an ion concentration suitable for battery operation, and conversely, if it exceeds this range, the viscosity of the electrolyte increases, reducing the mobility of lithium ions and increasing the decomposition reaction of the lithium salt itself, which may reduce the performance of the battery, so the concentration is appropriately adjusted within this range.
[0087] The organic solvent contained in the non-aqueous electrolyte may be any organic solvent commonly used in electrolytes for lithium secondary batteries, without limitation. For example, ethers, esters, amides, linear carbonates, cyclic carbonates, etc. may be used alone or in combination.
[0088] The ether-based compound may include acyclic ethers and cyclic ethers.
[0089] For example, the acyclic ether may be at least one selected from the group consisting of dimethyl ether, diethyl ether, dipropyl ether, methyl ethyl ether, methyl propyl ether, ethyl propyl ether, dimethoxyethane, diethoxyethane, ethylene glycol ethyl methyl ether, diethylene glycol dimethyl ether, diethylene glycol diethyl ether, diethylene glycol methyl ethyl ether, triethylene glycol dimethyl ether, triethylene glycol diethyl ether, triethylene glycol methyl ethyl ether, tetraethylene glycol dimethyl ether, tetraethylene glycol diethyl ether, tetraethylene glycol methyl ethyl ether, polyethylene glycol dimethyl ether, polyethylene glycol diethyl ether, and polyethylene glycol methyl ethyl ether, but is not limited thereto.
[0090] As an example, the cyclic ether may be 1,3-dioxolane, 4,5-dimethyl-dioxolane, 4,5-diethyl-dioxolane, 4-methyl-1,3-dioxolane, 4-ethyl-1,3-dioxolane, tetrahydrofuran, 2-methylfuran, 2-methyltetrahydrofuran, 2,5-dimethyltetrahydrofuran, 2,5-dimethoxytetrahydrofuran, 2-ethoxytetrahydrofuran, 2-methyl-1,3-dioxolane, 2-vinyl-1,3-dioxolane, 2,2-dimethyl-1,3-dioxolane, 2-methoxy-1,3-dioxolane, 2-ethyl-2-methyl-1,3-dioxolane, tetrahydropyran, 1,4-dioxane, 1,2-dimethoxybenzene, 1,3-dimethoxybenzene, 1,4-dimethoxybenzene, isosorbide dimethyl ether, ether), but is not limited thereto.
[0091] The ester among the organic solvents may be any one selected from the group consisting of methyl acetate, ethyl acetate, propyl acetate, methyl propionate, ethyl propionate, propyl propionate, γ-butyrolactone, γ-valerolactone, γ-caprolactone, σ-valerolactone, and ε-caprolactone, or a mixture of two or more of these, but is not limited thereto.
[0092] Specific examples of the linear carbonate compound include, but are not limited to, any one selected from the group consisting of dimethyl carbonate (DMC), diethyl carbonate (DEC), dipropyl carbonate, ethyl methyl carbonate (EMC), methyl propyl carbonate, and ethyl propyl carbonate, or a mixture of two or more of these.
[0093] Specific examples of the cyclic carbonate compound include any one selected from the group consisting of ethylene carbonate (EC), propylene carbonate (PC), 1,2-butylene carbonate, 2,3-butylene carbonate, 1,2-pentylene carbonate, 2,3-pentylene carbonate, vinylene carbonate, vinylethylene carbonate, and halides thereof, or a mixture of two or more of these. Examples of halides thereof include, but are not limited to, fluoroethylene carbonate (FEC).
[0094] The electrolyte may contain lithium nitrate (LiNO3) as an additive in addition to the electrolyte salt and organic solvent. The inclusion of lithium nitrate has the effect of forming a stable coating on the lithium metal electrode, thereby improving charge / discharge efficiency.
[0095] The electrolyte injection may be performed at an appropriate stage during the manufacturing process of the electrochemical device depending on the manufacturing process and required properties of the final product, i.e., before assembly of the electrochemical device, at the final stage of assembly of the electrochemical device, etc. Injection of the electrolyte may allow the cell stack and the lithium nitrate film to be impregnated with the electrolyte.
[0096] The lithium secondary battery according to the present invention can be manufactured by laminating or stacking the separator and the electrodes and folding them in addition to the general winding process. The battery case can be cylindrical, prismatic, pouch-type, coin-type, etc. According to an embodiment of the present invention, the lithium secondary battery can be a cylindrical lithium secondary battery, a prismatic lithium secondary battery, a pouch-type lithium secondary battery, or a coin-type lithium secondary battery, and in particular, a pouch-type lithium secondary battery.
[0097] Hereinafter, preferred examples will be presented to aid in understanding the present invention. However, the following examples are merely illustrative of the present invention, and it will be apparent to those skilled in the art that various changes and modifications are possible within the scope of the scope and technical ideas of the present invention. It is to be understood that such changes and modifications fall within the scope of the appended claims.
[0098] <Manufacturing lithium-sulfur batteries> Example 1 An aqueous solution containing 2 wt% lithium-carboxymethylcellulose (Li-CMC) was prepared. Lithium nitrate (LiNO3) was added to the aqueous solution to prepare a coating composition. At this time, the weight ratio of the solid content of the lithium nitrate and lithium-carboxymethylcellulose was 93:7.
[0099] The coating composition was applied onto aluminum foil and coated with a Mathis coater (Mathis Switzerland, SV-M). After coating, the film was dried for 5 hours in an oven at 50°C, and then dried for 20 hours in an oven at 80°C to prepare a lithium nitrate-containing film.
[0100] Then, the lithium nitrate-containing film was rolled to finally produce a lithium nitrate-containing film.
[0101] A mixed solution was prepared by mixing a sulfur-carbon (CNT) composite (S:C = 75:25 (weight ratio)) as a positive electrode active material and a 3 wt% lithium-polyacrylic acid (Li-PAA) aqueous solution, with the weight ratio of the solids of the sulfur-carbon composite and lithium-polyacrylic acid being 95:5.
[0102] Additional water was added to the mixed solution to prepare a slurry having a solid content of 30 wt % based on the total weight of the mixed solution.
[0103] The slurry was applied onto an aluminum foil current collector, coated to a certain thickness using a Mathis coater (Mathis Switzerland, SV-M), and then dried at 50° C. for 2 hours to prepare a positive electrode.
[0104] A 30 μm-thick lithium metal thin film was used as the negative electrode.
[0105] The electrolyte was prepared by dissolving 0.75M LiFSI and 6% by weight of lithium nitrate (LiNO3) in an organic solvent mixture of 1,2-dimethoxyethane (DME) and 2-methylfuran (2-MeF) in a volume ratio of 3:7.
[0106] The positive and negative electrodes were placed facing each other with a 16 μm thick polyethylene separator interposed therebetween to prepare a cell stack.
[0107] The cell stack was placed in an aluminum pouch, and the lithium nitrate-containing film was inserted into the space between the cell stack and the pouch, i.e., the lithium nitrate-containing film was inserted onto one side of the outermost layer of the cell stack.
[0108] Then, an electrolyte was injected and the battery was sealed to prepare a lithium-sulfur battery.
[0109] Comparative Example 1 . A lithium-sulfur battery was manufactured in the same manner as in Example 1, except that the lithium nitrate-containing film was not used.
[0110] Experimental Example 1. Evaluation of the Coulombic efficiency of a lithium-sulfur battery The lithium-sulfur batteries prepared in Example 1 and Comparative Example 1 were evaluated for performance using a charge / discharge tester (PESCO5-0.01, PNE solution, Korea).
[0111] In the first three cycles, the charge / discharge capacity was measured from 2.5 to 1.8 V at a current density of 0.1 C, and from the fourth cycle, the battery was discharged at 0.3 C and charged at 0.2 C to measure the charge / discharge capacity.
[0112] Then, the coulombic efficiency of the lithium-sulfur batteries of Example 1 and Comparative Example 1 was calculated according to the following Equation 1, and the results are shown in Table 1 below.
[0113] [Mathematical formula 1] Coulomb efficiency (%) = (current cycle discharge capacity / previous cycle discharge capacity) x 100 [Table 1]
[0114] As shown in Table 1, the lithium-sulfur battery of Example 1 showed that the coulombic efficiency did not decrease even with the progression of cycles, but was maintained at a constant level.
[0115] However, the lithium-sulfur battery of Comparative Example 1 showed a decrease in coulombic efficiency as the number of cycles increased.
[0116] From this, it was found that the lithium-sulfur battery including the lithium nitrate-containing film continuously supplies lithium nitrate for a long cycle, and it was confirmed that the supply of lithium nitrate maintains high coulombic efficiency for a long period of time.
[0117] The decrease in coulombic efficiency means that some of the charged material was not discharged, which means that some of the active material was irreversibly changed, which has a direct impact on the degradation of the battery life.
[0118] The coulombic efficiency results after 200 cycles between Example 1 and Comparative Example 1 showed a difference of about 1%. As the lithium-sulfur battery undergoes repeated cycles, the irreversible capacity accumulates exponentially, and the 1% difference can cause a large difference. Therefore, maintaining the coulombic efficiency as high as possible plays a very important role in improving the lifespan of the lithium-sulfur battery. Therefore, the lithium-sulfur battery of Example 1 can be considered to have a much better lifespan characteristic than the lithium-sulfur battery of Comparative Example 1.
[0119] That is, the lithium-sulfur battery of the present invention can maintain high coulombic efficiency over a long cycle, thereby achieving excellent life characteristics.
[0120] Additionally, in order to confirm that the lithium nitrate-containing film supplies lithium nitrate when the battery is operated, the lithium nitrate-containing film was checked after the lithium-sulfur battery of Example 1 was operated. The color of the electrolyte was confirmed in the lithium nitrate-containing film. Since the lithium nitrate-containing film was in contact with the electrolyte, it was found that the lithium nitrate-containing film supplied lithium nitrate when the lithium-sulfur battery was operated. [Explanation of symbols]
[0121] 10: Cell stack 20: Positive electrode 30: Separation membrane 40: Negative electrode 50: Lithium nitrate carrier in the solid state
Claims
1. A cell stack including one or more unit cells each including a positive electrode, a negative electrode, and a separator interposed between the positive electrode and the negative electrode; A solid-state lithium nitrate carrier, Electrolyte, and a battery case containing the cell stack, a solid-state lithium nitrate holder, and an electrolyte; The positive electrode includes a positive electrode active material layer, The positive electrode active material layer contains sulfur, The negative electrode includes a negative electrode active material layer, the negative electrode active material layer contains lithium metal or a lithium alloy, The solid-state lithium nitrate holder is located on one or both sides of the outermost layer of the cell stack, The solid-state lithium nitrate holder is a film having a coating layer containing lithium nitrate and a binder formed on one or both sides of a substrate film, The solid-state lithium nitrate holder is located in a space between the battery case and the cell stack.
2. 2. The lithium secondary battery according to claim 1, wherein the coating layer comprises lithium nitrate and a binder in a weight ratio of solid content of 80:20 to 98:
2.
3. The positive electrode contains elemental sulfur (S 8 ), organic sulfur compounds (Li 2 S n (n≧1)), and carbon-sulfur polymers ((C 2 S x ) n 2. The lithium secondary battery according to claim 1, comprising one or more positive electrode active materials selected from the group consisting of: x = 2.5 to 50, n ≥ 2.
Citation Information
Patent Citations
Non-water electrolyte secondary battery
JP2006286313A
Electrolyte for lithium sulfur cells
JP2007518229A
Cell, and electrolyte for cell
JP2016066595A
Electrochemical cells comprising electrolyte additives and ionomer articles, and methods for making and using the same
KR1020150032670A
Lithium-sulfur battery cell electrode
US20180019471A1